The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1111/j.1365-2044.2007.05432.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of hospital costs associated with traumatic brain injury in England and Wales*

Abstract: SummaryUsing data from the Trauma Audit Research Network, we investigated the costs of acute care in patients ‡ 18 years of age hospitalised for traumatic brain injury between January 2000 and December 2005 in England and Wales. Traumatic brain injury patients were defined and stratified using the Abbreviated Injury Scale. A total of 6484 traumatic brain injury patients were identified; 22.3% had an Abbreviated Injury Scale score of three, 38.0% of four and 39.7% of five. Median age (IQR) was 42 years (28-59) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 12 publications
4
33
0
Order By: Relevance
“…Previous observational studies, consistent with cost data in HITS-NS, suggest large incremental differences in costs between management in specialist and non-specialist centres. 3,41 Disparities of this magnitude are less likely to be explained by confounding, suggesting that our parameterisation may indeed reflect reality. However, ultimately, evidence from a well-conducted randomised trial is necessary to provide a definitive estimate.…”
Section: Interpretation Of Findingsmentioning
confidence: 92%
See 3 more Smart Citations
“…Previous observational studies, consistent with cost data in HITS-NS, suggest large incremental differences in costs between management in specialist and non-specialist centres. 3,41 Disparities of this magnitude are less likely to be explained by confounding, suggesting that our parameterisation may indeed reflect reality. However, ultimately, evidence from a well-conducted randomised trial is necessary to provide a definitive estimate.…”
Section: Interpretation Of Findingsmentioning
confidence: 92%
“…Each patient with TBI costs an average of £15,000 for acute NHS care, a figure which increases if the patient is admitted to a SNC. 3 Subsequent rehabilitation costs are also significant, but both are dwarfed by costs to society from premature death or lifelong dependency as a young adult. Observational evidence at the time of applying for funding in 2008 suggested that this NHS investment had failed to reduce case fatality from TBI over the 1994-2003 decade, with recent trials of neuroprotective agents failing to identify any single new effective therapy.…”
Section: Relevance Of Hits-ns To the Nhsmentioning
confidence: 99%
See 2 more Smart Citations
“…In developed countries, the annual incidence rates are approximately 200 per 100,000 [1]. The greater the severity of TBI, the greater the economic burden on healthcare providers [2,3], particularly acute care and rehabilitation services.…”
Section: Introductionmentioning
confidence: 99%